Penggunaan Peta Konsep untuk Meningkatkan Kemampuan Menulis Karangan Deskripsi Siswa Kelas IV - Yulmainar Yulmainar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Implementation of conventional learning is assumed as causing of the lack of students’ motivation. Hence, ability of the fourth grade students at SDN 06 V Koto Kampung Dalam Kabupaten Padang Pariaman in writing essay was low. This research was aimed to improve students’ ability in writing essay by using the concept mapping. Subject of research were the fourth grade students at SDN 06 V Koto Kampung Dalam Kabupaten Padang Pariaman. This class action research was held in two cycles. Data of research were obtained through observation and assessment of students’ work including the mapping concept, outline of essay, and whole essay. Data were analyzed qualitatively and quantitatively. Researcher set the standard of students’ learning achievement as 80%. After cycle I, students; learning achievement is 77,34%. Standard of students’ learning achievement was exceeded after cycle II, i.e. 86,36%. The result of research indicates that implementation of concept mapping can improve students’ ability in writing essay.